Genetic Characterization and Estimation Variety Eight of Papaya Genotype - Siti Hafsah; . Yusnizar; . Firdaus (Syiah Kuala University, 2015)
Characterization and prediction of genetic diversity is one of the stages on the papaya plant breeding activities in obtaining the parent plant in accordance with a predetermined idiotipe. Karaktersasi doneafter exploration and germplasm collection is done. Currently the plant breeding laboratory studiesprogram Agrotechnology Faculty of Agriculture has some papaya genotypes were successfully collected is from the cross, a collection of some areas, collection of research centers Tropical Fruits IPB Bogor and Fruit Research Institute Solok. The general objective is to get a papaya plant breeding better varieties from existing varieties (new idiotipe). Papaya plant characteristics desired by idiotype is a strong plant, short stature and quick to bear fruit, tree hermaphrodite, not the formation of stamens karpeloid (imperfect) or sterile, resistant to pests and diseases and high production. Characteristics of preferred fruit is sweet, flavorful soft, smooth fruit skin, thick flesh is red, round cavity and its shelf-life longer. The study was conducted in Gardens Farmers in Saree Aceh Besar, using eight genotypes of papaya exploration results. Experiments using a completely randomized design were repeated three times. The parameters observed qualitative and quantitative characters on vegetative and generative phase. The results showed that genotype Calina have short stature and fast fruiting as well as high production potential. Merah delima genotype showed a slow germination and growth. From the eigth genotipe papaya tested showed high genetic diversity and high heritability. Therefore, the selection can be done in early generations